Effect of incorporation of microstructured carbonized cellulose on surface and mechanical properties of epoxy composites. Issue 27 (30th December 2019) - Bartoli, Mattia; Rosso, Carlo; Giorcelli, Mauro; Rovere, Massimo; Jagdale, Pravin; Tagliaferro, Alberto; Chae, Michael; Bressler, David C.
ABSTRACT: In this study, we reported the use of cellulose derived microstructured biochars for the production of reinforced plastics. Cellulose nanocrystals and wasted cotton fibers were used as cellulose template structures and converted into carbonaceous materials under pyrolytic conditions. Biochars particles were produced with the shape of deformed spheres or rods and dispersed into an epoxy matrix with a loading ranging from 1 wt % to 10 wt %. Biochar‐based composites showed remarkably elongation properties of up to 8.2% using 2 wt % of carbonized cellulose nanocrystals and a very low friction coefficient of 0.22 using 10 wt % of carbonized cotton fibers. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48896. HIGHLIGHTS: Carbon spheres and carbon rods were produced through pyrolytic conversion of cellulose nanocrystals and wasted cotton fibers. Mechanical properties of carbon spheres and carbon rods epoxy composites were studied showing the differences induced by the particle shapes. An ultimate tensile strength improvement of 57% was reached using 5 wt % of carbonized cellulose nanocrystals. A maximum elongation improvement of 100% was reached using 2 wt % of carbonized cellulose nanocrystals. A friction coefficient reduction of 61% was reached using 10 wt % of carbonized cotton fibers. Abstract :